If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(x + -4) + -1 = 7x + 3 Reorder the terms: 5(-4 + x) + -1 = 7x + 3 (-4 * 5 + x * 5) + -1 = 7x + 3 (-20 + 5x) + -1 = 7x + 3 Reorder the terms: -20 + -1 + 5x = 7x + 3 Combine like terms: -20 + -1 = -21 -21 + 5x = 7x + 3 Reorder the terms: -21 + 5x = 3 + 7x Solving -21 + 5x = 3 + 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. -21 + 5x + -7x = 3 + 7x + -7x Combine like terms: 5x + -7x = -2x -21 + -2x = 3 + 7x + -7x Combine like terms: 7x + -7x = 0 -21 + -2x = 3 + 0 -21 + -2x = 3 Add '21' to each side of the equation. -21 + 21 + -2x = 3 + 21 Combine like terms: -21 + 21 = 0 0 + -2x = 3 + 21 -2x = 3 + 21 Combine like terms: 3 + 21 = 24 -2x = 24 Divide each side by '-2'. x = -12 Simplifying x = -12
| 7w+11=3w-25 | | (4w+3)(5w-8)=0 | | x/2+x/3=3/4 | | -3n=87 | | 3x-21=x+73 | | -x+44=21 | | 21-3g=20+2g | | 5a+4a-6b= | | (9-p)3= | | y=0.5x^3-2x+2.5 | | e^2+7e+10= | | 2c+19=65 | | p(-4)=-9+p | | 16(3x-.25)= | | 0.5x^3-2x+2.5=y | | (z+5)(z-8)=0 | | 0.5x^3-2x+2.5=0 | | -4=-(x-3)+6(x-2) | | 5(c-8-3)-3(2c+12)=-84 | | 2x+x+2=5x-10 | | .05x+.10(200-x)=.45x | | 0.09w=1.8 | | (a+4)(a+5)=0 | | -132=-39 | | -(c+10)+3(2c-6)= | | -132=39 | | -3v-v=16 | | -9b=-117 | | 35x+9=55 | | -n+2n=4 | | -8b=-117 | | -7x-3=4 |